Działania amerykańskich biskupów katolickich na rzecz ofiar wykorzystywania seksualnego przez duchownych. Wytyczne Komisji do spraw Ochrony Dzieci i Młodzieży - KŁOS-SKRZYPCZAK, ALEKSANDRA (Teologia i Moralność, 2020)
The American Catholic Church for more than two decades faced with a crisis through in connection with the sexual abuse of minors. The article presents the actions of American bishops for victims of sexual abuse by clergy in both preventive and preventive care. The fi rst part presents the functioning of the Committee for the Protection of Children and Young People, then discusses the most important, recently published documents relating to the sexual abuse of minors.